2002
DOI: 10.1097/00005537-200208000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tracheal and Subglottic Tears in Neonates

Abstract: Early detection of airway rupture by flexible endoscopy is essential for timely diagnosis and appropriate treatment. Standard endotracheal intubation can exacerbate the problem and should be deferred if possible until direct airway visualization can be accomplished. Signs associated with tracheal tears include subcutaneous emphysema, respiratory distress, pneumothorax, and pneumomediastinum. These should lead to emergent consultation with otolaryngologists for examination and securing of the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
16
1
Order By: Relevance
“…5,6 There are also reports about spontaneous tracheal ruptures as a complication of difficult delivery. 7 In our study, by contrast, iatrogenic lesions during intubation were the main cause of tracheal injury. Many causes of intubation-related tracheal injury have been cited.…”
Section: Discussionmentioning
confidence: 47%
“…5,6 There are also reports about spontaneous tracheal ruptures as a complication of difficult delivery. 7 In our study, by contrast, iatrogenic lesions during intubation were the main cause of tracheal injury. Many causes of intubation-related tracheal injury have been cited.…”
Section: Discussionmentioning
confidence: 47%
“…[6][7][8] The laceration usually occurs longitudinally in the posterior membranous wall of the trachea or at the junction between the membranous wall and cartilaginous ring. [4][5][6]9 Most tracheal ruptures occur in the lower third of the trachea. Another common area of rupture is the cricothyroid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This can also occur in neonatal or pediatric cases of tracheal rupture after a complicated vaginal delivery or minimal blunt cervical trauma. 2,[9][10][11] The development of the clinical symptoms and signs of tracheal rupture depends on the dissection of air through the tissue planes from the initial wound. 9 The air leaking from a laryngotracheal rupture spreads through the soft tissue planes of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of the cases of pneumomediastinum go undetected when only the anteroposterior view is considered. One study suggested that x-ray alone detected only 30% of the spontaneous pneumomediastinum cases 9) . Another study suggested that chest CT was required for diagnosis 10) .…”
Section: Introductionmentioning
confidence: 99%